Central Obesity Incidence in Students of Public Health Department, Universitas Negeri Gorontalo Based on Fiber Intake - Sunarto Kadir; Maksum, Tri Septian (International Journal of Public Health Excellence (IJPHE), 2023)
Central obesity is excess fat accumulation in abdominal area. Prevalence of central obesity in Gorontalo Province has exceeded the national prevalence (36.6%) based on results of Basic Health Research in 2018. Adolescents of reproductive age are one of the risk groups for central obesity due to an imbalance in food consumption intake and energy use. This study aims to analyze central obesity incidence in students of Public Health Department, Universitas Negeri Gorontalo based on fiber intake. This type of research is an analytic survey with a cross-sectional study design. Instruments used include 3x24 hour food recall and nutrisurvey to measure fiber intake and a measuring tape to measure waist circumference. Research sample was 120 people obtained using simple random sampling technique. Data analysis technique uses a simple logical regression test. The results showed that all respondents had less fiber intake (100.0%), and at most did not have central obesity (85.0%). There is an effect of fiber intake on the incidence of central obesity (p=0.003; OR=0.854). It is recommended for students to manage their diet by choosing the right ingredients, increasing consumption of vegetables and fruits by 1 to 3 servings per day and always doing sports and physical activity regularly.